)
4x+10x=28
у=2х
у=2х
14х=28
x=2
y=4
(2;4)
2u-v=3
10u=4
v=2u-3
u=0,4
v=0,8-3
u=0,4
v=-2,2
u=0,4
(0,4 ;-2,2)
p=3q+1
p^2-9q=7
p=3q+1
(3q+1)²-9q⇒ это можно в уме 9q+6q+1-9q=7
p=3q+1
6q=6
p=4
q=1
(4;1)
x=2z
y=z-3
2z+z-3+z=9
4z=12⇒z=3
y=3-3=0
x=3*2=6
(6;0;3)
#22222222222
a=3b
2b=34-5
2b=29
a=3*14,5
(b=14,5
a=43,5
(14,5; 43,5)
- q=2-3p⇒q=3p-2
5p-3*(3p-2)=-6
5p-9p+6=-6
q=3p-2
-4p=-12
q=3*3-2
p=3
q=7
(3;7)
u=1+2q
(u-2q)(u+2q)=5
u=1+2q
u+2q=5 ⇒2q+1+2q=5
u=1+2q
4q=4
u=1+2*1⇒u=3
q=1
(3;1)
z=4x
y=x+2
x+2*(x+2)-4x=3
x+2x+4-4x=3⇒ -x=-1
x=1
z=4
y=1+2=3
(1;3;4)
a){y+2x=-5
{x^2+y^2=25
{y=-5-2x
{x^2+(-5-2x)^2=25
x^2+4x^2+10x+25=25
5x^2+10x=0
5(x^2+2x)=0
x^2+2x=0
x(x+2)=0
x=0
x+2=0
x=-2
y=-5-2*-2=-9
y=-5-2*0=-5
ответ (0 -2) (-9 -5)
б)
{y=x^2+6x+7
{y-2x=4
y=4+2x
y=x^2+6x+7
4+2x=x^2+6x+7
x^2+4x+3=0
D=16-4*1*3=V4=2
x=-4+2/2=-1
x2=-6/2=-3
y=4+2*-1=-2
y2=4+2*-3=-2
ответ (-1 -3) (-2 -2)
в)
{xy-2y-4x=-5
{x-3y=-10
x=-10+3y
(-10+3y)y-2y-4(-10+3y)=-5
-10y+3y^2-2y+40-12y=-5
3y^2-24y+45=0
D=4
y=3
y=5
x=-10+3*3=-1
x=-10+3*5 =5
ответ (3 5 ) ( -1 5)